2020
DOI: 10.29374/2527-2179.bjvm107820
|View full text |Cite
|
Sign up to set email alerts
|

Renal nephroblastoma in an adult dog

Abstract: The study was carried out at Hospital Veterinário,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…In this case, the mass was sufficiently large to occupy half of the abdominal cavity and was 16.5% of the body weight. In previous studies, RCC did not attain sufficiently massive size to occupy half of the abdominal cavity (10,12,14), however, nephroblastoma could be massive (1,13) × 2, 7 × 5 × 7, 12 × 6, and 8 × 7 × 5 cm) were observed in medium-and large-breed dogs including Collie, Alsatian, Boxer, Afghan, and Labrador (12). Furthermore, in human, RCC with a diameter of >20 cm is extremely rare and can be diagnosed as a huge RCC (4).…”
Section: Discussionmentioning
confidence: 91%
“…In this case, the mass was sufficiently large to occupy half of the abdominal cavity and was 16.5% of the body weight. In previous studies, RCC did not attain sufficiently massive size to occupy half of the abdominal cavity (10,12,14), however, nephroblastoma could be massive (1,13) × 2, 7 × 5 × 7, 12 × 6, and 8 × 7 × 5 cm) were observed in medium-and large-breed dogs including Collie, Alsatian, Boxer, Afghan, and Labrador (12). Furthermore, in human, RCC with a diameter of >20 cm is extremely rare and can be diagnosed as a huge RCC (4).…”
Section: Discussionmentioning
confidence: 91%
“…A literature review identified 21 case reports and one retrospective study evaluating five reported cases (Table 2). [1][2][3][4][5]7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In the literature, variable tumour biological features have been reported. Historically, survival times have been very poor, with the survival time ranging 0-6 months in the 2006 retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…German shepherd dogs and labrador retrievers are overrepresented for canine spinal cord nephroblastoma 6 . Reported survival times are varied, ranging from 12 days to 33 months 1,7 . In both veterinary and human medicine, nephrectomy, with or without adjuvant chemotherapy, is the treatment of choice for unilateral renal nephroblastoma 3,5,6,8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal nephroblastoma is uncommon in dogs, but reported cases include juvenile and adult dogs, which are treated by nephrectomy with or without adjuvant chemotherapy and have a high metastatic rate (50%) and various survival times (5). Although renal nephroblastoma is most often diagnosed in young dogs (1), case reports of adult animals predominate in the literature (1,5,16,19,25).…”
mentioning
confidence: 99%